The Washback effect of the Iranian University entrance examination on Pre-University English Teachers. - Ghorbani, Mohammad Reza (2008)
This study examines the nature and scope of the washback impact of the university entrance examination (UEE) on pre-university English teachers’ (PETs) perceptions. Teaching experience, educational background, professionalism, and gender were studied as independent variables. Based on stratified random sampling, 377 PETs were selected to respond to the questionnaires. Eight PETs were also purposively selected to participate in two focus group interviews. Pearson product moment and t-test were used to analyze the quantitative data from the survey questionnaires and a systematic note-based technique recommended by Kruger (2002) was used to analyze the qualitative data from the focus group interviews. The findings show that only PETs’ perceived professionalism in teaching was associated with their perceptions (r = .38). All of the interviewed PETs perceived the negative effect of the UEE and expected the authorities to reform it based on the current teaching and testing theories.